Functions of WTO, IMF, World Bank, and UNCTAD. - Elboyev Otajon Polvonquliyevich (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
Annotation: This article provides an in-depth analysis of the key functions of major global economic institutions, including the World Trade Organization (WTO), International Monetary Fund (IMF), World Bank, and the United Nations Conference on Trade and Development (UNCTAD). It explores how these organizations contribute to international trade, economic stability, poverty reduction, and sustainable development. The WTO is highlighted for its role in promoting free trade and resolving trade disputes, while the IMF focuses on financial stability and providing monetary support to member countries. The World Bank’s efforts in funding development projects and reducing poverty are examined, along with UNCTAD’s focus on integrating developing countries into the global economy. This article serves as a comprehensive guide for understanding the complementary roles these institutions play in fostering global economic cooperation.